2010
DOI: 10.1007/s00214-010-0793-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of approaches to estimate the resonance energy

Abstract: We discuss Ab Initio approaches to calculate the energy lowering (stabilisation) due to aromaticity. We compare the valence bond method and the block-localised wave function approaches to calculate the resonance energy. We conclude that the valence bond approach employs a Pauling-Wheland resonance energy and that the block-localised approach employs a delocalisation criterion. The latter is shown to be more basis set dependent in a series of illustrative calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Only in the case of 19 the VB-EC and SCI do not agree, whereas the VB-EC and NICS(1) give opposite predictions in 21. In half of the studied systems (17,20,21,22) the results of the HOMA and VB-EC go along, but not for 15, 16, 18 and 19. It should be pointed out that in the previous study [65], it has been shown that the HOMA does not agree with the other aromaticity indices in aza naphthalenes.…”
Section: Tablementioning
confidence: 88%
See 2 more Smart Citations
“…Only in the case of 19 the VB-EC and SCI do not agree, whereas the VB-EC and NICS(1) give opposite predictions in 21. In half of the studied systems (17,20,21,22) the results of the HOMA and VB-EC go along, but not for 15, 16, 18 and 19. It should be pointed out that in the previous study [65], it has been shown that the HOMA does not agree with the other aromaticity indices in aza naphthalenes.…”
Section: Tablementioning
confidence: 88%
“…Ring Table 8 Correlation coefficients for the relations between different aromaticity indices and VB-EC of the hexagonal rings in aza derivatives of naphthalene (15)(16)(17)(18)(19)(20)(21)(22). R ef 0.3373 SCI 0.7947 SCI NAO 0.9611 HOMA 0.6068 NICS (1) À0.8123 Table 6 Coulson-Chirgwin weights of Kekulé structures of naphthalene and its aza derivatives obtained with the 6-311G(d,p) basis set ( Fig.…”
Section: Compmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzene is among the most studied systems in chemistry. This emblematic molecule is an annulene composed of 6 carbon atoms displaced on a D 6h symmetric planar ring, and its geometric, electronic and magnetic properties are still reasons for scientific inquiry . From the energetic point of view, the molecule is more stable than their cyclic polyenes analogues.…”
Section: Many Electron Chemical Bondsmentioning
confidence: 99%
“…In fact, the aromatic stabilization energy, ASE, is most often studied. This is estimated in such a way that energy is (usually) only gained through π-electron delocalization [12,29,30].…”
Section: Introductionmentioning
confidence: 99%